2005
DOI: 10.1080/07315724.2005.10719449
|View full text |Cite
|
Sign up to set email alerts
|

Beverage Consumption Patterns in Elementary School Aged Children across a Two-Year Period

Abstract: Shifts in beverage consumption were found in this convenient sample across two years. Diet soda consumption was the only type of beverage associated with year 2 BMI Z-score, and consumption was greater in overweight subjects and subjects who gained weight as compared to normal weight subjects at two years. Additional longitudinal data examining associations between beverage consumption and BMI is needed in children and adolescents, as consumption of regular and diet soda has become more of a social norm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
185
2
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(205 citation statements)
references
References 16 publications
9
185
2
8
Order By: Relevance
“…Interestingly, children who were overweight/obese at baseline but had acceptable BMI at follow-up consumed significantly lower amounts of soft drink/cordial compared to children who were overweight/obese at follow-up, further substantiating a role for soft drinks in excess weight gain. In contrast to findings from earlier studies, 6,7 increased sweetened beverage did not displace milk consumption in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, children who were overweight/obese at baseline but had acceptable BMI at follow-up consumed significantly lower amounts of soft drink/cordial compared to children who were overweight/obese at follow-up, further substantiating a role for soft drinks in excess weight gain. In contrast to findings from earlier studies, 6,7 increased sweetened beverage did not displace milk consumption in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…This could be because soda may explain a greater proportion of variability in energy intake compared with the other snacking items in this population. These results are in line with those from several longitudinal studies conducted in children from developed countries that have demonstrated a link between soda consumption and BMI (9,(37)(38)(39)(40) . A recent randomized trial among school-age children showed that sugar-sweetened beverages caused greater gains in BMI and WC compared with unsweetened beverages (41) .…”
Section: Discussionsupporting
confidence: 92%
“…In the entire US population, soft drink intake has increased over the last two decades while dairy product consumption has declined. 39,[44][45][46]60,61,[64][65][66][67] However, despite such reports, no correlation was seen between decreased calcium intake and soft drink consumption in adolescent girls using data from the US CSFII (1994)(1995)(1996). 68 Reporting an observational study of 268 children born in western Sydney (the Nepean Study), Tam et al found increased sweet drink intakes did not displace milk consumption.…”
Section: Consumption Of Sweet Drinks Juices and Milk By Childrenmentioning
confidence: 99%